EFEKTIVITAS METODE COOPERATIVE LEARNING TYPE TEAMS GAMES TOURNAMENT (TGT) DALAM PEMBELAJARAN HURUF HIRAGANA SISWA KELAS XI SMK TIGAMA PEKANBARU - Atriani, Shelti; Sinaga, Mangatur; Isnaini, Zuli Laili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the level of ability to read hiragana letters of class XI student of Pekanbaru TIGAMA vocational school before and after the cooperative learning method type teams games tournament. The sample of the research is the second grade (class XI) students of Pekanbaru TIGAMA Vocational school which consists of 16 students. Data collection was carried out by using test technique. The tes given consistts of 25 objective questions and 5 essay items. This study applied two tests, namely pretest and posstest. The average value of thw results of the pretest obtained by students was 30.25 and the posstest average increased 45,19 becoming 75,44. Thus, there was a significant efect on the ability level of the second grade students of pekanbaru TIGAMA Vocational School to write and read hiragana letters after applying the cooperative learning method type tams games tournamnet.Key Words: Cooperative Learning Type Teams Games Tournament